2021
DOI: 10.3390/s21093134
|View full text |Cite
|
Sign up to set email alerts
|

On Supporting University Communities in Indoor Wayfinding: An Inclusive Design Approach

Abstract: Mobility can be defined as the ability of people to move, live and interact with the space. In this context, indoor mobility, in terms of indoor localization and wayfinding, is a relevant topic due to the challenges it presents, in comparison with outdoor mobility, where GPS is hardly exploited. Knowing how to move in an indoor environment can be crucial for people with disabilities, and in particular for blind users, but it can provide several advantages also to any person who is moving in an unfamiliar place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…A total of ten studies focused on accessibility in High Educational Institution (Delnevo et al, 2018;Dinc Uyaroglu, 2021;Eldridge et al, 2022;Lawrence, 2021;Ozdemir & Sungur, 2022;Porto et al, 2022;Prandi et al, 2021;Rafferty, 2011;Torkildsby, 2017, seven studies focus on Student with Disabilities ((Dinc Uyaroglu, 2021; Edwards & Larson, 2022;Parker et al, 2021;Porto et al, 2022;Rantanen et al, 2015;Vogt et al, 2022), eight studies discussed on Universal Design theory and new term of UD (Dinc Uyaroglu, 2021; Edwards & Larson, 2022;Nah & Lee, 2016;Ozdemir & Sungur, 2022;Prandi et al, 2021.;Torkildsby, 2017;Van Eck et al, 2022;Xu et al, 2022, and out twenty-two studies, twelve concentrated on outdoor environment Boeri et al, 2020;Bozkurt, 2021;Delnevo et al, 2018;Dinc Uyaroglu, 2021;Gasparovic & Sladovic, 2021;Nah & Lee, 2016;Parker et al, 2021, Prandi et al, 2021, Rantanen et al, 2015Samsudin et al, 2019;van Eck et al, 2022;Ytterhus & Åmot, 2021. In addition, ten studies applied qualitative approach while two studies employed a mix methods (qualitative + quantitative) approach. The remaining studies (10) used quantitative analysis methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of ten studies focused on accessibility in High Educational Institution (Delnevo et al, 2018;Dinc Uyaroglu, 2021;Eldridge et al, 2022;Lawrence, 2021;Ozdemir & Sungur, 2022;Porto et al, 2022;Prandi et al, 2021;Rafferty, 2011;Torkildsby, 2017, seven studies focus on Student with Disabilities ((Dinc Uyaroglu, 2021; Edwards & Larson, 2022;Parker et al, 2021;Porto et al, 2022;Rantanen et al, 2015;Vogt et al, 2022), eight studies discussed on Universal Design theory and new term of UD (Dinc Uyaroglu, 2021; Edwards & Larson, 2022;Nah & Lee, 2016;Ozdemir & Sungur, 2022;Prandi et al, 2021.;Torkildsby, 2017;Van Eck et al, 2022;Xu et al, 2022, and out twenty-two studies, twelve concentrated on outdoor environment Boeri et al, 2020;Bozkurt, 2021;Delnevo et al, 2018;Dinc Uyaroglu, 2021;Gasparovic & Sladovic, 2021;Nah & Lee, 2016;Parker et al, 2021, Prandi et al, 2021, Rantanen et al, 2015Samsudin et al, 2019;van Eck et al, 2022;Ytterhus & Åmot, 2021. In addition, ten studies applied qualitative approach while two studies employed a mix methods (qualitative + quantitative) approach. The remaining studies (10) used quantitative analysis methods.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 12 studies reported that outdoor environments consist of few lists which are main entrance, pedestrian path, pedestrian crossing, curb or ramp, sidewalk, tactile or material, parking OKU, dropoff, way finding and outdoor education. Detecting obstacles in outdoor environments is an important problem for blind people who desire to move autonomously (Prandi, Delnevo, et al, 2021). According to (Dinc Uyaroglu, 2021), case-based situation does not lead them to participate in diverse educational activities.…”
Section: Outdoor Environmentmentioning
confidence: 99%
“…They deployed GPS and an inertial measurement unit on electric wheelchairs. Prandi et al [100] developed an IoT system that provides indoor wayfinding functionality to improve indoor mobility. They used smart beacons as sensors to locate people.…”
Section: Accessibilitymentioning
confidence: 99%
“…In the study and development of HBI, there is a need to understand differences in engagement and support required across different genders, age ranges (i.e., including children, youth, and older adults), and socioeconomic statuses 110 . Moreover, HBI solutions and technologies should determine how support is equitable and inclusive for individuals from communities of color and people with varied physical abilities or mental health conditions 111 , 112 . Finally, there is an opportunity to expand HBI efforts to support the needs of displaced groups, migrants, and unsheltered individuals 113 .…”
Section: Hbi Research Dimensionsmentioning
confidence: 99%